Preventing radicalisation and terrorism in Europe : a comparative analysis of policies - Maniscalco, Maria Luisa; Rosato, Valeria (Cambridge Scholars Publishing, 2019)
Within the general framework of the European TRIVALENT project, the comparative analysis presented here focuses, alongside policy measures taken at EU level, on counter-terrorism and counter-radicalisation policies implemented by five European countries; namely, Belgium, France, Italy, Spain and the United Kingdom. These case studies with their peculiarities and differences offer insights into the role of long-term and structural factors in defining counter-terrorism and counter-radicalisation policies, and highlight the influence that specific occurrences can have. The volume analyses differe.